Plain Beasts: The Social Dimension and Animalistic Presence of Dogs in Fontane’s Frau Jenny Treibel and Effi Briest - Amir Zelinger (Recherches Germaniques)
This article offers a posthumanist reading of two of Theodor Fontane’s novels, Frau Jenny Treibel and Effi Briest. Focusing in particular on the introduction of dogs at various points in the novels, it maintains that although the canine characters play only a marginal role in the development of the plot it is precisely their ostensibly negligible appearance that endows them with a substantial meaning. Using the insights of posthumanism allows thereby for the discerning of the animalistic significance in Fontane’s realism, which, as is well known, deals primarily with social issues and tends to concentrate fundamentally on human aspects. The very down-to-earth and at times purely material presence of the dogs in both works helps to broaden the image of society drawn by Fontane and makes it appear more complex and unconventional. The combination between social realism and unassuming animalness as exemplified by Fontane’s doggish creatures, as the article concludes, could then also provide us with a more solid understanding of the place of the social in animal-based posthumanist symbolism.